Enhancing perovskite solar cells efficiency via dual surface passivation - Refka Sai; Shrouq H. Aleithan (PLoS ONE, 2026)
Effective defect passivation is essential for achieving high performance in perovskite solar cells (PSCs). Dimensional engineering provides a powerful strategy to suppress non-radiative recombination in both the bulk and surface regions of PSCs. In this work, we present a novel interfacial passivation approach for the perovskite/hole transport layer interface using a dual-cation passivation layer composed of guanidinium bromide (GuaBr) and n-phenylethylammonium bromide (n-PEABr). This dual-cation strategy delivers an open-circuit voltage of 1.23 V and a power conversion efficiency (PCE) of 25.11%, significantly outperforming devices based on single-cation passivation. The combined cations induce the formation of a mixed 1D/2D perovskite structure, resulting in a more uniform and hydrophobic surface compared with unpassivated films. Moreover, stability tests conducted under ambient conditions (80% relative humidity) and continuous light-soaking reveal markedly enhanced device stability. The results demonstrate the superior passivation effectiveness of phenylethylammonium compared with previously reported methods. In particular, this approach surpasses the 23% PCE achieved using octylammonium passivation, achieving efficiencies exceeding 25%. Overall, the excellent defect passivation and favorable optical and electrical properties of phenylethylammonium play a key role in significantly improving both the efficiency and stability of PSCs.